A proposed instructional module on the concept "change" for first year high school - Benitez, Cynthia Bello 1946- (1977)
The purpose of the study was to make a proposed module on the concept "change" in social studies I for first year high school. The different periodicals, books and magazines on individualized instruction and instructional modules were examined. The module is composed of the following parts: introduction, pre-test, objectives, modular activities, post-test, and answers to the test. The study found out that the use of modules relieves the teacher of being a transmitter of knowledge and a programmer-director but he becomes a co-designer and assister. A module trains the learner to build techniques and skills on attacking learning problems, thus he learns how to learn.